In-situ cross-linking strategy for efficient and operationally stable methylammoniun lead iodide solar cells - Xiaodong Li (Nature Portfolio, 2018)
The stability of perovskite solar cell remains the biggest challenge that hinders its commercialization. Here Li et al. incorporate crosslinkable molecules to form a crosslinked perovskite film and increase the device operational stability by 590 times to 400 h under standard Xenon lamp without filters.